Modal Sosial dan Kesuksesan Pedagang Intan Kota Martapura, Kabupaten Banjar, Provinsi Kalimantan Selatan - Yusuf Hidayat (DIMENSI - Jurnal Sosiologi, 2017)
This paper is the result of research focused on the study of the importance of social capital in diamonds trading as a rare commodity in Martapura City. This research has been done in Martapura city with qualitative research method and has been interviewed as many as 5 people as informant. This study found that the form of social capital in trading diamonds was trust and social network, reciprocity in a joint venture formed by diamond traders and subscription relationships formed in the sale and purchase of diamonds. Social capital has an important meaning in the success of diamond trading because with the social capital of traders it can muster the power to acquire and market diamonds as a rare and speculative commodity.